2011
DOI: 10.1016/j.kjms.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal hippocampal N‐methyl‐d‐aspartate glutamatergic and δ‐opioidergic systems modulate anxiety behaviors in rats in a noninteractive manner

Abstract: The present study aimed to investigate the effects of N-methyl-d-aspartate (NMDA)-type glutamate receptor agonist, NMDA, on anxiety-like behavior induced by δ-opioid receptor agents in rats, using the elevated plus maze instrument. The dorsal hippocampus (CA1) is known to play an important role in anxiety formation and modulation. Bilateral administration of different doses of δ-opioid receptor agonist, [d-pen2,5] enkephalin acetate hydrate (1 μg/rat, 2 μg/rat, 5 μg/rat, and 10 μg/rat; 1 μL/rat; 0.5 μL/rat in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Our results are in agreement with the previous investigation showing that NMDA agonist releases behavioural and anxiolytic-like behaviours indicating the role of NMDA receptors in modulation of anxiety-related behaviours [26,73]. Moreover, there is also an investigation showing that the activation of NMDA receptor induces anxiogenic-like effects in EPM and social interaction tasks [21].…”
Section: Effects Of Intra-nac Shell Nmda Administration On Anxiolyticsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with the previous investigation showing that NMDA agonist releases behavioural and anxiolytic-like behaviours indicating the role of NMDA receptors in modulation of anxiety-related behaviours [26,73]. Moreover, there is also an investigation showing that the activation of NMDA receptor induces anxiogenic-like effects in EPM and social interaction tasks [21].…”
Section: Effects Of Intra-nac Shell Nmda Administration On Anxiolyticsupporting
confidence: 93%
“…With respect to the preferential agonists, at least three subtypes have been identified for glutamate, including N-methyl-D-aspartate (NMDA), AMPA and kainate [57]. Investigations have revealed that the NMDA receptor plays a critical part in regulation of learning, memory formation (possibly through long-term potentiation and depression) [9,38] and anxiety-related behaviours [26,46,63,73,78]. A plethora of anatomical experiments have demonstrated that there are close relationships between NAc glutamatergic and dopaminergic systems [66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, we also showed that long-term memantine administration at doses of 5, 10, or 20 mg/kg leads to an anxiogenic phenotype that is manifested by decreased time spent in the light compartment (light–dark box) and reduced time spent in open arms (elevated plus-maze). Interestingly, a previous work showed that the administration of MK801, another non-competitive NMDAR antagonist, to rats induced an anxiety-like phenotype in the elevated plus-maze ( Solati, 2011 ). In contrast to MK801, high doses of memantine (100 mg/kg) increased time spent in open arms, implying an anxiolytic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid peptides play a role in many functions, including pain perception, respiration, homeothermy, nutrient intake, and the immune response. Moreover, studies have demonstrated the role of opioid receptors in regulating baseline anxiety states and related behaviors (Roeska et al, 2008;Solati 2011;McHugh et al, 2017;Wang et al, 2017). These functions are mediated by three major classes of G protein-coupled receptors, µ, δ and κ, whose activation inhibits adenylyl cyclase (Kahveci et al, 2006).…”
Section: The Effect Of Opioid System On Anxiety Behaviormentioning
confidence: 99%